When Necessity Begets Ingenuity: Scavenging for Survival in a Globalizing City - Oteng-Ababio, M. (Centre for African Studies, 2012)
This paper describes how due to lack of formal job opportunities, e-waste scavenging has emerged as a major livelihood (survival) strategy for a rapidly growing urban population. It documents how the process has been fueled by neo-liberal economic policies adopted since 1983 that not only failed to create a “vibrant urban economy” but also exacerbated the unemployment and under-employment rates and created a general economic crisis. The study relied on both qualitative and quantitative data as well as discussions and interviews with stakeholders, affected, and interested persons to provide data for analysis. The paper explores the various aspects of their work: economic, financial, environmental and social. Since the equipment has both pollution and resource potentials, the need for proper control and monitoring of the informal handling and recycling practice is highlighted. The study calls for the formalization of the informal activity not only to sustain the livelihood for the urban poor but also for efficient e-waste management
Keywords: e-waste, scavenging, livelihood, environmental health, Accra